2019
DOI: 10.1175/jcli-d-18-0513.1
|View full text |Cite
|
Sign up to set email alerts
|

The Onset of the Indonesian–Australian Summer Monsoon Triggered by the First-Branch Eastward-Propagating Madden–Julian Oscillation

Abstract: The Madden–Julian oscillation (MJO) often causes the onset of the Indonesian–Australian summer monsoon (IASM) over Indonesia and northern Australia. In the present study, a composite analysis is conducted to reveal the detailed IASM onset process and its air–sea interactions associated with the first-branch eastward-propagating MJO (FEMJO) based on 30-yr ERA-Interim data, satellite-derived sea surface temperature (SST), outgoing longwave radiation (OLR), and SODA3 ocean reanalysis. The results distinctly illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 89 publications
5
10
0
Order By: Relevance
“…This result is relevant to Yang et al (2019), and we suggest that the South Java sea shelf and its adjacent area can be classified as mesotrophic according to Antoine et al (1996). Figure 7C, D shows that high Chl-a occurs during the SE monsoon from May to November and low during the NW monsoon from December to March, which is consistent with previous studies (Duan et al, 2019;Wyrtki, 1962). Chl-a began to rise one month earlier at the eastern (May) than at the western (June) points (Figure 7C, D) and peaked in September.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is relevant to Yang et al (2019), and we suggest that the South Java sea shelf and its adjacent area can be classified as mesotrophic according to Antoine et al (1996). Figure 7C, D shows that high Chl-a occurs during the SE monsoon from May to November and low during the NW monsoon from December to March, which is consistent with previous studies (Duan et al, 2019;Wyrtki, 1962). Chl-a began to rise one month earlier at the eastern (May) than at the western (June) points (Figure 7C, D) and peaked in September.…”
Section: Discussionsupporting
confidence: 91%
“…Located between two oceans, which are the Indian ocean and the Pacific ocean, the strength of the South Java upwelling can be affected by oceanic and atmospheric dynamics such as monsoons (Wyrtki, 1962;Duan et al, 2019), tides (Ffield and Gordon, 1996;Rudiastuti et al, 2019), the Madden-Julian Oscillation (MJO) (Duan et al, 2019), Kelvin and Rossby waves (Cipollini et al, 2001;Iskandar, 2005;Menezes and Vianna, 2019;Pujiana and McPhaden, 2020;Syamsudin, 2004), the Pacific to Indian ocean water masses flowing through the Indonesian archipelagos called the Indonesian Through Flow (ITF) (Cipollini et al, 2001;Menezes and Vianna, 2019), the South Java Coastal Current (SJCC) (Soeriaatmadja, 1957;Quadfasel & Cresswell, 1992;Sprintall et al, 1999;Gingele et al, 2002;Utari et al, 2019), South Equatorial Current (SEC) (Ningsih et al, 2020), eddies Yang et al, 2019;Ismail et al, 2021), marine heatwaves (Iskandar et al, 2021), the Indian Ocean Dipole (IOD) (Saji et al, 1999;Gualdi et al, 2003;Wirasatriya et al, 2020), and El Niño/Southern Oscillation (Susanto and Gordon, 2001; ENSO; e.g. Gualdi et al, 2003;Susanto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There are many other studies motivated by YMC and addressing YMC issues using data from satellites, global reanalysis products, and numerical models. These studies cover a wide range of topics, such as the diurnal cycle (Baranowski et al, 2019), MJO propagation over the MC (Burleyson et al, 2018; Pang et al, 2018) and its barrier effect (DeMott et al, 2018; Ling et al, 2019), atmospheric waves (Ruppert & Zhang, 2019; Takasuka et al, 2019), aerosol (Bagtasa et al, 2018; Cohen et al, 2018; Koplitz et al, 2018), the monsoon (Diong et al, 2019; Duan et al, 2019), the ITF and the ocean in general (Cao et al, 2019; Gordon et al, 2019; Hu et al, 2019; Liang et al, 2019), and prediction and predictability (Wang et al, 2019).…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…It is well noted that the remarkable seasurface temperature (SST) warming occurs off the coast of northern Australia during the premonsoon period, and the subsequent IASM onset always coincides with the arrival of the active Madden-Julian oscillation (MJO; Hendon and Liebmann, 1990a;Kawamura et al, 2002;Wheeler and McBride, 2005). It was recently further revealed that a robust phase-locking relationship exists among the regional SST maximum north of Australia, the first-branch eastwardpropagating MJO (FEMJO) originating from the tropical southwestern Indian Ocean, and the IASM onset (Duan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%